(3GdYbhO GdeHQeI HhGSWI GdYedGA GdGdcJhfjjf GdCPcjGAs - (3fQjeGf eSYhO(B, (3HhQZOIs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2019)
(3eONd Gdi Yejd GdPcGA GdGUWfGYj,h OhQGdYejd GdGdcJQhfj chSjW aj eYGedGJ GdJLGQI GdEdcJQhfjI, eY PcQ BdjI GHQGe GdYbhO HhGSWJg hGdNWhGJ GdJegjOjI hGdJaGhV GdGSJOdGdj, GVGaI Edi GdeTGcd GdbGfhfjI ddJYGbO HhGSWI GdYedGA GdGdcJQhfjjf GdCPcjGA eY GdCSGS GdbGfhfj dfaGP gPg GdYbhO,hcPdc UYhHI JaSjQ GdGdJRGe GdJYGbOj deSJNOe GdYejd GdGdcJQhfj HfGAG Ydi fXQjI GdGQGOI, haUd GdGdJRGe GdJYGaOj deSJNOe GdYejd GdGdcJQhfj Yf GQGOJg GdJYGbOjIhCNjQG GVaGA GdWGHY GdeGOj Ydi GdEQGOI GdJYGbOjI hGbJQGM GSJHOGd GdGQGOI GdfaSjI deSJNOe GdYejd GdGdcJQhfj HGdeUdMI GdJj jQej GdjgG(B.s
(3eQGLY U(B.317s
Keywords: (3GdJLGQI GdEdcJQhfjIs; (3GdJLGQI(B-(3EdcJQhfjGJs; (3GdPcGA GdGUWfGYjs